Physical activity participation and mental health profiles in Canadian medical students: latent profile analysis using continuous latent profile indicators. Issue 6 (3rd July 2021) - McFadden, Taylor; Fortier, Michelle; Sweet, Shane N.; Tomasone, Jennifer R.
ABSTRACT: Rates of mental illness among Canadian medical students are higher than age-, gender-, and education-matched peers. One predictor of mental health is physical activity; though the relationship between different intensities of physical activity and mental health has not been investigated in medical students. The purpose of this study was to examine relationships between physical activity and mental health profiles in a sample of Canadian medical students. A total of N = 125 students completed an online survey. Latent profile analysis was performed to identify distinct profiles using four continuous latent profile indicators (emotional well-being, social well-being, psychological well-being, resilience). Three mental health profiles emerged, showing low ( n = 18), moderate ( n = 72) and high ( n = 36) self-reported ratings of mental health. The classification quality was good (entropy = 0.81). Individuals in the high mental health profile engaged in more mild physical activity ( M = 144.28 mins/week; SD  = 22.12) and less moderate-to-vigorous physical activity ( M = 195.86 mins/week; SD  = 25.67) compared to students in the moderate and low profiles, though not significantly. This suggests that mild physical activity might be the most effective intensity in supporting mental health among medical students, though further research is recommended.